A Study of Enhanced Heterogeneous Ice Nucleation in Simulated Deep Convective Clouds Observed During DC3. Issue 23 (4th December 2018) - Takeishi, Azusa; Storelvmo, Trude
Abstract: The impacts of enhanced heterogeneous ice nucleation (HET) on the properties of deep convective clouds (DCCs) have been investigated in cloud‐resolving simulations with the WRF‐CHEM model. The study focuses on a case observed during the Deep Convective Clouds and Chemistry (DC3) field campaign. For the simulated DCCs, which had cold cloud‐base temperatures, an inverse relationship exists between ice crystal mass produced through HET and anvil ice crystal number concentrations. This seems to be due to the indirect competition between HET and subsequent homogeneous freezing (HOM) for liquid droplets. Furthermore, our simulations suggest that HET enhancements at warmer temperatures are more efficient in depleting liquid droplets below and hence have larger impacts on anvil properties than HET enhancements at colder temperatures do. This temperature dependence indicates that similar increases in the number of ice nucleating particles (INPs) may potentially have different impacts on DCCs, depending on the INP type and at which temperatures they can nucleate ice crystals. We also found that the reduced anvil ice number concentrations due to the enhanced HET may lead to optically thinner anvil clouds. The reduction in cloud optical depth comes from a decrease in ice crystal mass concentrations, and in some runs also from an increase in ice crystal sizes. These results suggest potentially large impacts of INPs on the properties of DCCs, especially if precipitation is predominantly produced through ice processes in the DCCs. The results underscore the importance of fully understanding the temperature‐dependent ability of aerosol particles to nucleate ice crystals. Key Points: Enhanced heterogeneous ice nucleation in deep convective clouds with a cold cloud‐base temperature may lead to optically thinner anvils The impacts of enhanced heterogeneous ice nucleation are especially pronounced when the enhancement occurs at warmer temperatures Our findings are likely most applicable to clouds in which warm‐rain processes do not contribute much to the total precipitation